Growth promotion and resistance induction against anthracnose in cucumber using Trichoderma spp. - da Silva, Veronica Nogueira; Guzzo, Sylvia Dias; Lucon, Cleusa Maria Mantovanello; Harakava, Ricardo (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the effect of 60 isolates ofTrichoderma and the product Trichodermil on the growth promotion and on the induction of systemic resistance to anthracnose caused byColletotrichum lagenarium in cucumber, and to identify isolates ofTrichoderma spp. effective as resistance inductors. In the assays of growth promotion, the Trichoderma spp. isolates were inoculated in the substrate and, after 21 days, the shoot dry weight of the plants was measured. In the experiments of resistance induction, the isolates which promoted growth were inoculated in the substrate, at the base of the plants, seven days beforeC. lagenarium inoculation in the leaves. The isolate which showed the best performance was evaluated for anthracnose symptom reduction in applications at 3, 7 or 14 days before the pathogen inoculation, and for its ability of increasing the peroxidase activity. Nineteen isolates and Trichodermil promoted cucumber growth up to 100% and conferred plant protection against anthracnose up to 88.39%. The isolate IB 31/06 reduced the disease severity at the evaluated time intervals. No significant peroxidase increase was observed seven days after treatment with IB 31/06, in the plants treated and infected with the pathogen, in comparison to infected plants. Gene sequencing of the 19 isolates allowed for the identification of seven Trichoderma different species.
Keywords: Colletotrichum lagenarium; Cucumis sativus; antagonism; biocontrol; induced systemic protection; peroxidase